Indications for elective neck dissection in cT1N0M0 oral cavity cancer according to the AJCC eight edition: A nationwide study. (May 2023) - Chien, Chih-Yen; Wang, Cheng Ping; Lee, Li-Yu; Lee, Shu-Ru; Ng, Shu-Hang; Kang, Chung-Jan; Lin, Jin-Ching; Terng, Shyuang-Der; Hua, Chun-Hung; Chen, Tsung-Ming; Chen, Wen-Cheng; Tsai, Yao-Te; et al.
Highlights: NCCN maintains that END should be considered for cT1-2N0M0 OCSCC with a DOI > 3 mm. DOI > 2.5 mm and poor differentiation predict adverse outcomes in cT1N0M0 OCSCC. The decision to perform END should be guided by DOI and tumor differentiation. This strategy allows avoiding END in 48.6% of patients, without compromising outcomes. Abstract: Objectives: According to the NCCN guidelines, there is weak evidence to support the use of elective neck dissection (END) in early-stage oral cavity squamous cell carcinoma (OCSCC). We sought to examine the indications for END in patients with cT1N0M0 OCSCC defined according to the AJCC Staging Manual, Eight Edition. Methods: Of the 3886 patients diagnosed with cT1N0M0 included in the study, 2065 underwent END and 1821 neck observation. Results: The 5-year outcomes for patients who received END versus neck observation before and after propensity score matching (n = 1406 each) were as follows: neck control, 96 %/90 % (before matching), p < 0.0001; 96 %/90 % (after matching), p < 0.0001; disease-specific survival (DSS), 93 %/92 % (before matching), p = 0.0227; 93 %/92 % (after matching), p = 0.1436. Multivariable analyses revealed that neck observation, depth of invasion (DOI) > 2.5 mm, and poor differentiation were independent risk factors for 5-year outcomes. Upon the application of a scoring system ranging from 0 (no risk factor) to 3 (presence of the three risk factors), the following 5-year rates were observed: neck control, 98 %/95 %/84 %/85 %; DSS, 96 %/93 %/88 %/85 %; and overall survival, 90 %/86 %/79 %/59 %, respectively (all p < 0.0001). The survival outcomes of patients with scores of 0 and 1 were similar. The occult metastasis rates in the entire study cohort, DOI > 2.5 mm, and poor differentiation were 6.8 %/9.2 %/17.1 %, respectively. Conclusion: Because all patients who received neck observation had a score of 1 or higher, END should be performed when a DOI > 2.5 mm or poorly differentiated tumors are present. Under these circumstances, 48.6 % (1888/3886) of cT1N0M0 patients may avoid END without compromising oncological outcomes.